Enhancement of the photocurrent and electrochemical properties of the modified nanohybrid composite membrane of cellulose/graphene oxide with magnesium oxide nanoparticle (GO@CMC.MgO) for photocatalytic antifouling and supercapacitors applications. (1st October 2021) - El-Shafai, Nagi M.; Beltagi, Amr M.; Ibrahim, Mohamed M.; Ramadan, Mohamed S.; El-Mehasseb, Ibrahim
Highlights: Improvement the electrochemical properties and charge transfer of GO@CMC.MgO NHM. Multi-function nanocomposites for photocatalytic anti-fouling and solar cell applications. The photocatalytic process with organic compounds pollution has been detected. The supercapacitor and energy application have been revealed. Abstract: A novel nanohybrid material (NHM) of magnesium oxide nanoparticle (MgO NPs) and modified antifouling membrane surface of graphene oxide nanosheet (GO) and carboxymethylcellulose (CMC) has been created via precipitation and ultrasonication methods, then characterized via various techniques for a novel antifouling membrane for water treatment, and supercapacitor applications for energy applications. The electrochemical properties of nanohybrid material (NHM) have been synthesized successfully by the cyclic voltammetry technique for detecting charge transfer, supercapacitor, and energy storage. Also, the optical properties of NHM antifouling nanomembrane have been detected by zeta potential and UV-spectroscopy apparatus for the following the generation of electrons, charge transfer, and formation of the reactive oxygen species (ROS) for oxidation of the organic materials pollutants for water treatment. The electron transfer of GO@CMC.MgO has been revealed via the photocatalytic process for the degradation of organic and inorganic pollutions. The supercapacitor and energy applications have been detected via the measurements of electrochemical impedance spectroscopy (EIS) by Nyquist plots, the following results have been obtained: - A good electron transfer has been detected with GO@CMC.MgO NHM. - The photocatalytic process with organic compounds pollution has been detected. - The supercapacitor and energy application have been revealed. The Results demonstrated that the fabricated NHM is promising electrode material for supercapacitor applications, energy storage and water treatment. Graphical abstract: Image, graphical abstract